Decoupling carbon emissions from economic growth in China’s textile industry: a decomposition of driving factors - Hong, Yuanxiao; Ma, Lindong; Kang, Song; Zhang, Guoqiang (Frontiers in Environmental Science, 2025)
As the world’s largest producer, consumer, and exporter of textiles and apparel, China plays a pivotal role in the carbon emission reduction of the industry. This paper employs the “Tapio” decoupling model to analyze the decoupling relationship between carbon emissions and economic growth in China’s textile industry across 30 provinces from 2001 to 2020. The LMDI model is then used to decompose the influencing factors of carbon emissions, followed by a comparative study of four distinct periods and three regions. The findings reveal that: (1) From 2001 to 2020, both carbon emissions and GDP growth in China’s textile industry exhibited a “rise then decline” trend. Carbon emissions primarily stemmed from coal consumption, followed by gasoline and natural gas. The energy structure had been gradually optimized, with the shares of coal and gasoline in total consumption declining, while the share of natural gas has increased. (2) Carbon emissions in China’s textile industry had achieved strong decoupling from economic growth over the 20-year study period. The decoupling status at different periods was as follows: weak decoupling (2001–2005), weak decoupling (2006–2010), strong decoupling (2011–2015), and weak negative decoupling (2016–2020). Comparing different regions, Central China exhibited strong decoupling, while East China and West China both experienced weak decoupling. (3) Per capita output value was the main driving factor behind the growth of carbon emissions, while energy consumption intensity factor played the most significant role in inhibiting emissions. Additionally, employment scale factor promoted carbon emissions in the first two periods but significantly suppressed them in the last two periods. The energy structure factor gradually strengthened its suppressive effect on carbon emissions, although its overall impact remained limited. Finally, based on these findings, feasible and practical policy recommendations are proposed.